2021
DOI: 10.1530/ec-21-0265
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and acid-base imbalance in severe COVID-19

Abstract: Acute systemic diseases, such as severe infections, can lead to electrolyte and acid-base alterations. To study the presence of electrolyte imbalance in severe COVID-19, we investigated the frequency and consequences of changes in electrolyte and acid-base patterns over time. We performed a retrospective cohort study including 406 patients with severe COVID-19. Levels of electrolytes, base excess, pH, serum osmolality and hematocrit, the first two weeks of hospitalization, were collected daily from the laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 33 publications
4
29
1
Order By: Relevance
“…This is in line with previous reports showing that dysnatremia (hypernatremia or hyponatremia) is a risk factor for mortality in patients with COVID-19 [ 30 , 31 ]. The dynamics of sodium are an important indicator of the severity of COVID-19, and dysnatremia is reportedly common and associated with a longer hospital stay and a higher risk of death [ 31 ]. We also identified hyperkalemia to be a risk factor for mortality.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with previous reports showing that dysnatremia (hypernatremia or hyponatremia) is a risk factor for mortality in patients with COVID-19 [ 30 , 31 ]. The dynamics of sodium are an important indicator of the severity of COVID-19, and dysnatremia is reportedly common and associated with a longer hospital stay and a higher risk of death [ 31 ]. We also identified hyperkalemia to be a risk factor for mortality.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have found that both high and low [ 32 ] potassium levels are risk factors for mortality. In our study, acidosis was also observed to be a risk factor for death, which is similar to previous reports [ 31 , 32 ]. Other laboratory findings that were associated with mortality (anemia, leukocytosis, thrombocytopenia, high aPTT, high INR, high troponin, and high ferritin) have also been reported to be risk factors for death in patients with COVID-19 [ 33 , 34 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was discovered that hypernatremia is very common in severe COVID-19. 49 The increased incidence of hypernatremia seems to be associated with a significant water loss during the disease. 50 The results obtained indicated a correlation between micro and macro elements in the blood and urine of patients with coronavirus.…”
Section: Resultsmentioning
confidence: 99%
“…As far as Na is concerned, Alkattan et al [ 157 ] did not observe any significant changes in the level of this element in the serum of severe versus non-severe COVID-19 patients, but other studies showed a significant reduction in the concentration of Na in the serum/plasma of patients with a severe form of COVID-19, in comparison with a group with mild disease [ 188 , 192 ] ( Table S2 ). Sjöström et al [ 193 ], who explored the dynamics of electrolytes in COVID-19 patients, revealed the presence of hyponatremia in subjects at admission followed by the development of hypernatremia during the first 2 weeks of hospitalization. As observed, hypernatremia was common and associated with a more severe COVID-19 course and a higher mortality rate.…”
Section: Covid-19: Elementsmentioning
confidence: 99%